(untitled) - Micietova, Maria; Sulgan, Marian (Doprava a spoje, 2010)
This article discusses problems of identifying and labeling logistic units, for example boxes, pallets and containers. Its aim is to bring the basic information about labeling logistic units across Europe with an internationally accepted numbering and bar coding system - the GS1 System